A systematic revision of the Shovel-nosed Salamander (Plethodontidae: Desmognathus marmoratus), with re-description of the related D. aureatus and D. intermedius - Pyron, R. Alexander; Beamer, David A. (Zootaxa, 2023)
Shovel-nosed Salamanders, Desmognathus marmoratus (Moore, 1899), were long thought to represent a single species from the southern Appalachian Mountains of the eastern United States, ranging from northeastern Georgia to extreme southwestern Virginia. These populations have a highly derived ecomorphology, being fully aquatic with a specialized flattened and elongated phenotype adapted to rocky riffle zones in fast-flowing, high-gradient mountain streams. Because of this, they were originally described in a separate genus, Leurognathus Moore, 1899. Four additional species or subspecies were described from 1928–1956 based on regional geographic variation in phenotype before being synonymized with L. marmoratus in 1962, which was reassigned to Desmognathus in 1996. Molecular analyses subsequently revealed four distinct candidate lineages in two distantly related clades, which were recently re-delimited into three species. These are D. aureatus (Martof, 1956) from northeastern Georgia, D. intermedius (Pope, 1928) from western North Carolina, and D. marmoratus from northwestern North Carolina. We provide a systematic revision of these taxa, which do not represent a natural group but instead exhibit convergent phenotypes across multiple species, potentially driven by ancient episodes of adaptive introgression between ancestral lineages. Our recent fieldwork revealed an astonishingly disjunct and morphologically distinct population of D. marmoratus in the New River Gorge of West Virginia, which were previously confused with D. kanawha Pyron and Beamer, 2022. This locality is 120 airline km away from the nearest populations of D. marmoratus in Virginia. No Shovel-nosed Salamanders have ever been found in the New River drainage during our extensive previous explorations or credibly reported in museum specimens or the literature. Additional cryptic populations of these taxa may remain.